What's turning the wheel? The theological hub of Song of Songs - S. Fischer (Acta Theologica)
Different interpretations are evaluated for their contribution towards a better under-standing of the theology of Song of Songs. Chapter 4:16-5:1 is presented as the structural centre of Song of Songs. Linear, cyclic and concentric structures point to the centrality of this passage. It has a key-function for the theology of the book which is understood as creational theology because love recalls paradise. God is identified with the third voice, encouraging the lovers to enjoy love in all its fullness.